Influence of genetic drift on patterns of genetic variation: The footprint of aquaculture practices in Sparus aurata (Teleostei: Sparidae). Issue 12 (23rd June 2019) - Cossu, Piero; Scarpa, Fabio; Sanna, Daria; Lai, Tiziana; Dedola, Gian Luca; Curini‐Galletti, Marco; Mura, Laura; Fois, Nicola; Casu, Marco
Abstract: Aquaculture finfish production based on floating cage technology has raised increasing concerns regarding the genetic integrity of natural populations. Accidental mass escapes can induce the loss of genetic diversity in wild populations by increasing genetic drift and inbreeding. Farm escapes probably represent an important issue in the gilthead sea bream ( Sparus aurata ), which accounted for 76.4% of total escapees recorded in Europe during a 3‐year survey. Here, we investigated patterns of genetic variation in farmed and wild populations of gilthead sea bream from the Western Mediterranean, a region of long gilthead sea bream farming. We focused on the role that genetic drift may play in shaping these patterns. Results based on microsatellite markers matched those observed in previous studies. Farmed populations showed lower levels of genetic diversity than wild populations and were genetically divergent from their wild counterparts. Overall, farmed populations showed the smallest effective population size and increased levels of relatedness compared to wild populations. The small broodstock size coupled with breeding practices that may favour the variance in individual reproductive success probably boosted genetic drift. This factor appeared to be a major driver of the genetic patterns observed in the gilthead sea bream populations analysed in the present study. These results further stress the importance of recommendations aimed at maintaining broodstock sizes as large as possible and equal sex‐ratios among breeders, as well as avoiding unequal contributions among parents.